Safety of Nonporous Silica Nanoparticles in Human Corneal Endothelial Cells. Issue 1 (December 2017) - Kim, Ja-Yeon; Park, Joo-Hee; Kim, Martha; Jeong, Hyejoong; Hong, Jinkee; Chuck, Roy; Park, Choul
Abstract Nonporous silica nanoparticles (SiNPs) are promising drug carrier platforms for intraocular drug delivery. In this study, we investigated the safety of three different sizes of SiNPs (50, 100, and 150 nm) in a human corneal endothelial cell (HCEC) line, B4G12. The HCECs were exposed to different concentrations (0, 25, 50, and 100 µg/ml) of three sizes of SiNPs for up to 48 h. Cellular viability, autophagy, lactate dehydrogenase (LDH) assay, and mammalian target of rapamycin (mTOR) pathway activation were evaluated. Intracellular distribution of the SiNPs was evaluated with transmission electron microscopy (TEM). TEM revealed that the SiNPs were up-taken by the HCECs inside cytoplasmic vacuoles. No mitochondrial structural damage was observed. Both cellular viability and LDH level remained unchanged with up to 100 µg/mL of SiNP treatment. Autophagy showed a significant dose-dependent activation with 50, 100, and 150 nm SiNPs. However, the mTOR activation remained unchanged. Human corneal tissue culture with 100 µg/ml concentrations of SiNPs for 72 h revealed no significant endothelial toxicity.In vivo corneal safety of the SiNPs (0.05 ml intracameral injection, 200 mg/ml concentration) was also verified in rabbit models. These findings suggested that 50, 100, and 150 nm SiNPs did not induce acute significant cytotoxicity in corneal endothelial cells at concentrations up to 100 µg/mL. However, long-term toxicity of SiNPs remains unknown.